California angel - Rosenberg, Nancy Taylor (New York : Signet, 1995)
"Is Toy Johnson an angel of mercy gifted with miraculous psychic powers? Or is this strikingly beautiful woman a kidnapper and killer, with a growing list of children as victims? Toy knows only that a near-death experience has launched her on a journey into the unknown. And now she is haunted by dreamlike memories of children she believes she somehow has saved. But if Toy sees herself as a living angel, that vision of herself is challenged when she is arrested and charged with murder."--Cover
National College of Business and Arts
Keywords: Angels -- Fiction; Religious fiction